Hayek and Mises:: From Vienna Days to Conceptions of the Market Process - Ebeling, Richard M. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
This article explains Friedrich A. Hayek and Ludwig von Mises personal and professional relationship during the period between the two World Wars, and explains their conceptions of the market process and the role of knowledge, prices and entrepreneurial expectations in tending to bring about competitive market coordination. Besides, it discusses those areas in which their approaches to these issues were complementary but not the same concerning expectations-formation in the market process.